The importance of the cultural dimension of food in understanding the lack of adherence to diet regimens among Mayan people with diabetes. Issue 17 (6th August 2019) - Juárez-Ramírez, Clara; Théodore, Florence L; Villalobos, Aremis; Allen-Leigh, Betania; Jiménez-Corona, Aida; Nigenda, Gustavo; Lewis, Sarah
Abstract: Objective: To understand non-adherence to medically recommended diets among Mayans with diabetes. Design: Using partially sequential mixed methods, questionnaires, semi-structured brief and in-depth interviews were applied. Questionnaire data were analysed with Pearson's χ 2 and Student's t tests and qualitative interviews with grounded theory microanalysis. Setting: Rural, predominantly Mayan communities in Chiapas, Quintana Roo and Yucatan, Mexico, 2008–2012. Participants: Purposive sample of Mayans with type 2 diabetes; using public health care; 168 women and twenty-seven men; age 21–50+ years. Results: Participants understood diabetes as caused by negative emotions, divine punishment, revenge via spells, chemicals in food and high sugar/fat consumption. Eliminating corn, pork, sugary beverages and inexpensive industrialized foods was perceived as difficult or impossible. More Mayans reporting not understanding physician instructions (30 v . 18 %) reported difficulty reducing red meat consumption ( P = 0·051). Non-adherence was influenced by lack of patient–provider shared knowledge and medical recommendations misaligned with local culture. Men whose wives prepared their meals, women who liked vegetables and young adults whose mothers prepared their meals reported greater adherence to dietary recommendations. Partial adherents said it made life tolerable and those making no physician-recommended dietary changes considered them too restrictive (they meant 'starving to death'). Over half (57 %) of participants reported non-adherence; the two principal reasons were dislike of recommended foods (52·5 %) and high cost (26·2 %). Conclusions: Adherence to dietary regimens in diabetes treatment is largely related to social and cultural issues. Taking cultural diversity, food preferences, local food availability and poverty into consideration is essential when developing health-promotion activities related to diabetes.